2005
DOI: 10.1007/s00330-005-2775-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the human brain in primary progressive multiple sclerosis with mapping of the spatial distributions using 1H MR spectroscopy and diffusion tensor imaging

Abstract: Primary progressive multiple sclerosis (ppMS; n=4) patients and controls (n=4) were examined by 1H magnetic resonance spectroscopy (MRS) and diffusion tensor imaging (DTI) in order to map choline (Cho), creatine and N-acetylaspartate (NAA), the fractional anisotropy (FA) and the apparent diffusion constant (ADC). After chemical shift imaging (point-resolved spectroscopy, repetition time/echo time 1,500 ms/135 ms) of a supraventricular volume of interest of 8x8x2 cm3 (64 voxels) MRS peak areas were matched to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 28 publications
6
28
0
Order By: Relevance
“…Among these neurochemical markers, N-acetylaspartate (NAA) expressed in neurons but not in glia [14]. Decreased NAA has been found in a number of disorders including brain tumors [15], epilepsy, and multiple sclerosis [16]. In addition to NAA, 1 H MRS also detects the choline moieties (Cho), which presumably reflect cell membrane integrity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these neurochemical markers, N-acetylaspartate (NAA) expressed in neurons but not in glia [14]. Decreased NAA has been found in a number of disorders including brain tumors [15], epilepsy, and multiple sclerosis [16]. In addition to NAA, 1 H MRS also detects the choline moieties (Cho), which presumably reflect cell membrane integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Because Cho is highly expressed in glial cells, changes in Cho level reflect changes in the number, size, and density of glial cells [17][18][19]. Thus, by measuring levels of NAA and Cho, neuronal and glial cell integrity in the brain can be decided [15,16]. Cr as a measure of cellular energy metabolism and usually taken as the standard denominator in MRS ratio analyses [14].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature supports its usefulness for the assessment of brain tumors, epilepsy, and other neurological disorders [1,2]. In the case of dementia, the medial temporal lobe (MTL) represents the focus of earliest and most pronounced tissue degeneration and metabolic alterations and therefore turns out to be a target of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lesion load seen on conventional MRI does not correspond very well to clinical manifestations of disease extent [3]. Several studies have shown that the white matter (WM) involvement is more extensive than shown on standard MRI [4][5][6][7][8][9][10][11]. The purpose of this study was to determine whether diffusion tensor imaging (DTI) of the cervical spinal cord in MS patients will allow us to establish reliable fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values of visible plaques as well as WM outside those visible lesions.…”
Section: Introductionmentioning
confidence: 99%